Current issues of the safety of the hospital – as a critical infrastructure (Academic Journal of Internal Affairs, 2023)
Aim: To explore the current security issues of in-patient care institutions from the perspective of critical infrastructure protection activities.Methodology: Examination of EU and national regulations on critical infrastructure, analysis of the legislative environment applicable to hospitals in security areas, based on practical experience.Findings: The regulation of critical infrastructure protection in the European Union and in Hungary is constantly evolving, and the development of further regulation affecting hospital safety is showing a mixed picture. The new EU Directive, which aims to increase resilience, will allow the introduction of standard methodological approaches that will impact on the complex security level of the hospital through the security of the patient care process.Value: The static operational critical infrastructure security planning practice has evolved over the past seven years, but further development of the planning methodology is needed to enable the organization to respond dynamically to the fundamental challenges of the healthcare sector and its ever-changing environment. To this purpose, standardized planning practices are available, applied and used in production at international level.
Keywords: critical infrastructure; hospital security; healthcare disaster; business continuity